Relacje między etyką, prawem i ekonomią: analiza poglądów Adama Smitha - Rogowska, Beata (Annales. Etyka w Życiu Gospodarczym, 2019)
Adam Smith is commonly viewed as the founding father of economics. This conviction stems from the publication of The Wealth of Nations in 1776. Smith’s works are chiefly examined in terms of economics. The discovery of reports of his Lectures on Jurisprudence and defining them as a “bridge” between his ethics, law and economics allows researchers to analyze Smith’s work from a fresh perspective. The aim of the paper is to discuss complex relationships between ethics included in The Theory of Moral Sentiments and general principles of law and economics. The main conclusion of this paper is that Smith emphasized the mutual complementation of moral and legal norms in the context of the economic development of the commercial society.